Kepadatan Telur Nyamuk Aedes Sp. Berdasarkan Warna Ovitrap dan Ketinggian Tempat di Kota Kupang - Jap, Novita; Setyobudi, Agus; Sahdan, Mustakim (Faculty of Public Health, Nusa Cendana University, 2019)
Mosquitos eggs desinty is influenced by ovitrap color and location altitude. Aedes sp. mosquistos prefer to lay their eggs on dark container and out of sun light. The recent study aims at finding out the Ovitrap Index (OI), the density level of Aedes sp. eggs, and analyze the eggs density on the basis of ovitrap colour and the location altitude at Kupang City. The population the study is all the mosquitos eggs found in the altitudes of 0-125 m asl, 126-250 m asl, and 251- 375 m asl. In this research the sample is all Aedes sp. mosquitos eggs found in every ovitrap at the three altitude levels. At each altitudes, 3 houses were choosen and in each house 3 light color ovitrap and 3 other of dark in color . The recent study found out that the Ovitrap Index of both light and dark in color at the altitudes of 0-125 m asl, 126-250 m asl, and 251-375 m asl is 100%, while OI at 251-375 m asl for the light ovitrap is 88,99% and dark ones is 100%. The eggs density is higher in dark ovitraps that is 305,67 eggs per ovitrap at 0-125 m asl but less in light ovitraps that is 92 eggs at the altitude of 126-250 m asl. There is no difference of eggs density level based on the color of the ovitrap found within houses in altitude of 0-125 m asl, and 251- 375 m asl. It is similar to eggs density outside of houses at 0-125 m asl and 251-375 m asl, density with p value= 0,02. There is also different eggs density between locayions altitude of 0-125 m asl and 126-250 m asl with p value= 0,031. However, it is found out that there is no correlation between level of eggs density and all levels of location altitudes.